Evaluating the predictive factors affecting outcome in patients with severe traumatic brain injury: a prospective observational study - Singh, Vikram; Nath, Amar; Beniwal, Meenu; Singh, Paritev; Dahiya, Rockey (International Surgery Journal, 2021)
Background: Severe traumatic brain injury (TBI) is a neurosurgical emergency and timely intervention is critical for favorable outcome. We aimed to evaluate certain demographic, clinical and radiological factors for outcome prediction in TBI patients in terms of morbidity and mortality. Methods: A prospective observational study was conducted in 100 patients of severe TBI admitted to our hospital from September 2016 to June 2018. Those with penetrating head injury, associated severe chest, abdominal or orthopedic trauma and pregnant or lactating women were excluded. Clinical outcome was assessed at the time of discharge and after three months according to Glasgow outcome score (GOS). Results: Majority of patients were adults in the age group 20 to 39 years. Road-side accident (75%) was the commonest mode of injury followed by fall (23%) and assault (2%). Out of 100 patients, 51 had in-hospital mortality. Of 49 patients who survived for GOS assessment at 3 months, three (6.1%) patients had unfavourable GOS I to III. Presence of hypoxemia, pupil non-reactivity, computerised tomography (CT) head findings of hemorrhagic contusion, subarachnoid hemorrhage (SAH), midline shift and effacement of basal cisterne were associated with significantly increased risk of unfavorable early and late outcome after severe TBI (p<0.05). Poor GCS score and fracture skull were associated with adverse early and late outcome respectively (p<0.001). Conclusions: Low GCS score at admission, pupil non reactivity, presence of hypoxemia, abnormal CT head findings (hemorrhagic contusion, SAH, midline shift and effacement of basal cisterne) were strong predictors of adverse outcome after severe TBI.